Evolução dos canais de distribuição de serviços financeiros no Brasil: um estudo sobre os correspondentes não-bancários e a atividade Econômica - Pinheiro, Anne Karolinne Nunes (2011)
Research has been devoted to the relationship between activity of the financial system and economic activity in different markets, including Brazil. There are arguments for this relationship in both directions. Brazil has a strong tradition of financing productive activity through the banking system. Despite the advances of the Brazilian economy in recent years and the strengthening of capital market observed since the year 1990, funding from the Brazilian company is still heavily based on the banking system. This work is a study on the evolution of the Brazilian Financial System, with emphasis on the present moment to strengthen the Distribution Channels of Financial Services (CDSF), specifically the segment of Non-Banking Correspondents. Combining the study of the financial system with the proposition that financial activity is able to stimulate economic activity, this study aims to analyze the evolution and performance of the Non-Banking Correspondents (a type of CDSF) and its potential ability to stimulate economic development since it act as intermediaries in financial services and lending for consumption and small businesses with limited access to the banking system. For the development of research, which has a descriptive and analytical, from an empirical research, it is contemplated two-fold: (i) Analysis of the performance and evolution of Distribution Channels for Financial Services Brazilians over the past two decades, describing conductors factors, the causes that contributed to its evolution and (ii) relational analysis between the Non-Banking Correspondents and Economic Activity in Brazil. We conducted an empirical research on the Brazilian market data from non-banking correspondents and economic activity statewide. The results showed that in the period 2001- 2008 was, in fact, a major growth segment in the Non-Banking Correspondents measured by the growing volume of funds intermediated by these agents. More importantly we have the empirical evidence found that the presence of agents Non-Banking Correspondents have explanatory power on economic activity in the country. Evidence in the opposite direction was also found as markers of economic activity also show segment on the explanatory power of Non-Banking Correspondents.